Digital communication education for children in conflict with the law (ABH) at LPKA class II Maros in the Sekolah Kebangsaan Program - Citra Rosalyn Anwar; Rita Gani; Asnur Lidayni (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2024)
This research analyzes the importance of digital communication education in improving election information literacy and critical thinking skills for children in conflict with the law (ABH) in LPKA Class II, Maros. As a vulnerable group as well as novice voters, they have the right to education that includes aspects of digital communication. The findings show that a lack of skills in digital communication and information management is one of the factors causing the problems experienced by these children. In the digital era, the ability to communicate effectively, including through digital media, is a fundamental skill in their social life. This study involved 50 children who are novice voters and participated in the Sekolah Kebangsaan program, which aims to strengthen digital literacy and critical thinking skills, especially related to election issues. This research is a case study with interviews, observation, and documentation data collection techniques during class. The results of the study show that the children in conflict with the law have developed communication skills, information management, confidence, and critical thinking, especially on election issues.